2018
DOI: 10.1146/annurev-chembioeng-060817-084025
|View full text |Cite
|
Sign up to set email alerts
|

Toward Constitutive Models for Momentum, Species, and Energy Transport in Gas–Particle Flows

Abstract: As multiscale structures are inherent in multiphase flows, constitutive models employed in conjunction with transport equations for momentum, species, and energy are scale dependent. We suggest that this scale dependency can be better quantified through deep learning techniques and formulation of transport equations for additional quantities such as drift velocity and analogies for species, energy, and momentum transfer. How one should incorporate interparticle forces, which arise through van der Waals interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(66 citation statements)
references
References 147 publications
(206 reference statements)
3
62
0
Order By: Relevance
“…In recent years the issue of the effect of the cell size on the numerical solution of fluidized bed has been addressed (Agrawal et al, 2001;Heynderickx et al, 2004;Igci et al, 2008;Parmentier et al, 2012;Ozel et al, 2013;Sundaresan et al, 2013). As discussed by Sundaresan et al (2013) the appropriate length scale for the grid resolution is is still an open issue and seems to be dependent on the given gas-solid flow configuration. However, Parmentier et al (2008) carried out an analysis of the effect of the grid resolution on dense fluidized beds with flow conditions roughly similar to the present study.…”
Section: Geometry and Meshmentioning
confidence: 99%
“…In recent years the issue of the effect of the cell size on the numerical solution of fluidized bed has been addressed (Agrawal et al, 2001;Heynderickx et al, 2004;Igci et al, 2008;Parmentier et al, 2012;Ozel et al, 2013;Sundaresan et al, 2013). As discussed by Sundaresan et al (2013) the appropriate length scale for the grid resolution is is still an open issue and seems to be dependent on the given gas-solid flow configuration. However, Parmentier et al (2008) carried out an analysis of the effect of the grid resolution on dense fluidized beds with flow conditions roughly similar to the present study.…”
Section: Geometry and Meshmentioning
confidence: 99%
“…Unfortunately, inhomogeneous mesoscale flow structures in such reactors are incredibly complex and manifest persistent instabilities in flow properties spanning all sorts of spatiotemporal scales 1‐3 . This dynamic nature is of fundamental importance in essential process features such as the interphase momentum, species, and heat transfer 4 . Development of accurate and reliable modeling methods for capturing such complex dynamics has been the grand challenge for FBR modelers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Cloete et al 14,30,31 presented the importance to include the physical anisotropic impacts in fTFM development, and they unveiled minor influences of increasing the SGM complexity via introducing additional markers. For more elaborate reviews, interested readers are referred to excellent articles of Schneiderbauer et al 32 and Sundaresan et al 4 Yet, despite multifarious contributions, better understanding subgrid closure modeling related to inhomogeneous structures and accurately predicting gas–particle flow hydrodynamics still pose prodigious challenges. For example, Cloete et al 14 indicated that a functional fitting method is commonly adopted in conventional filtered correlations; however, various model coefficients might have to be adjusted in such an approach.…”
Section: Introductionmentioning
confidence: 99%
“…The fast growth in supercomputing power has made computational fluid dynamics (CFD) a powerful tool for predicting detailed information of the flow and heat fields in gas–solid flows. However, the flow and heat transfer behavior in multiphase flow reactors cross a wide range of length and time scales . For example, mesoscale structures with sizes of 10–100 d p ( d p is the particle diameter), though stemming from the interphase interaction and transport behavior at the microscopic scale (1–5 d p ), significantly affect the overall flow dynamics and transport behavior at reactor scales .…”
Section: Introductionmentioning
confidence: 99%